Administration of single-dose GnRH agonist in the luteal phase in ICSI cycles: a meta-analysis - Oliveira, Joao Batista A. [UNESP]; Baruffi, Ricardo; Petersen, Claudia G. [UNESP]; Mauri, Ana L.; Cavagna, Mario; Franco, Jose G. [UNESP] (Biomed Central Ltd., 2010)
Background: The effects of gonadotrophin-releasing hormone agonist (GnRH-a) administered in the luteal phase remains controversial. This meta-analysis aimed to evaluate the effect of the administration of a single-dose of GnRH-a in the luteal phase on ICSI clinical outcomes.Methods: The research strategy included the online search of databases. Only randomized studies were included. The outcomes analyzed were implantation rate, clinical pregnancy rate (CPR) per transfer and ongoing pregnancy rate. The fixed effects model was used for odds ratio. In all trials, a single dose of GnRH-a was administered at day 5/6 after ICSI procedures.Results: All cycles presented statistically significantly higher rates of implantation (P < 0.0001), CPR per transfer (P = 0.006) and ongoing pregnancy (P = 0.02) in the group that received luteal-phase GnRH-a administration than in the control group (without luteal-phase-GnRH-a administration). When meta-analysis was carried out only in trials that had used long GnRH-a ovarian stimulation protocol, CPR per transfer (P = 0.06) and ongoing pregnancy (P = 0.23) rates were not significantly different between the groups, but implantation rate was significant higher (P = 0.02) in the group that received luteal-phase-GnRH-a administration. on the other hand, the results from trials that had used GnRH antagonist multi-dose ovarian stimulation protocol showed statistically significantly higher implantation (P = 0.0002), CPR per transfer (P = 0.04) and ongoing pregnancy rate (P = 0.04) in the luteal-phaseGnRH- a administration group. The majority of the results presented heterogeneity.Conclusions: These findings demonstrate that the luteal-phase single-dose GnRH-a administration can increase implantation rate in all cycles and CPR per transfer and ongoing pregnancy rate in cycles with GnRH antagonist ovarian stimulation protocol. Nevertheless, by considering the heterogeneity between the trials, it seems premature to recommend the use of GnRH-a in the luteal phase. Additional randomized controlled trials are necessary before evidence-based recommendations can be provided.